2010
DOI: 10.1128/jvi.02554-09
|View full text |Cite
|
Sign up to set email alerts
|

Venezuelan Equine Encephalitis Virus Capsid Protein Forms a Tetrameric Complex with CRM1 and Importin α/β That Obstructs Nuclear Pore Complex Function

Abstract: Development of the cellular antiviral response requires nuclear translocation of multiple transcription factors and activation of a wide variety of cellular genes. To counteract the antiviral response, several viruses have developed an efficient means of inhibiting nucleocytoplasmic traffic. In this study, we demonstrate that the pathogenic strain of Venezuelan equine encephalitis virus (VEEV) has developed a unique mechanism of nuclear import inhibition. Its capsid protein forms a tetrameric complex with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(150 citation statements)
references
References 52 publications
5
145
0
Order By: Relevance
“…In the case of SINV, helix I was shown to be responsible for dimerization of capsid molecules, required for virus assembly (17). In the case of VEEV, it was demonstrated to function as a nuclear export signal (NES) playing a critical role in inhibition of nuclear pore trafficking (36,37). In a recent study, we also showed that in VEEV capsid, SD2 was capable of accumulating adaptive mutations (35).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…In the case of SINV, helix I was shown to be responsible for dimerization of capsid molecules, required for virus assembly (17). In the case of VEEV, it was demonstrated to function as a nuclear export signal (NES) playing a critical role in inhibition of nuclear pore trafficking (36,37). In a recent study, we also showed that in VEEV capsid, SD2 was capable of accumulating adaptive mutations (35).…”
Section: Resultsmentioning
confidence: 84%
“…8B and C), which could result in higher infectious titers. The identified mutation was in an interesting position, in the capsid-specific NLS (36,37). SD2 has a common function in the alphaviruses in assembly of NC, but in VEEV it also functions as an NES (36,37), required for blocking the nuclear pores.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, NPC destabilization may result from the association of Nups and integrated proviral cDNA or nuclear vRNA during transcription (Capelson et al, 2010;Hou and Corces, 2010;Strambio-De-Castillia et al, 2010). HIV-1 may disrupt NPCs to evade antiviral responses, as seen in other viruses (Gustin and Sarnow, 2002;Fontoura et al, 2005;Bardina et al, 2009;Porter and Palmenberg, 2009;Atasheva et al, 2010;Ren et al, 2010). Another possibility is that encapsidated Nup62 may be required for efficient delivery of the PIC into the nuclei of newly infected cells (Fig.…”
Section: Nup62 Is Essential For Hiv-1 Vrna Exportmentioning
confidence: 99%
“…Alphaviruses also induce widespread host translational and transcriptional shut down in favour viral protein synthesis (Aguilar, Weaver et al 2007. The capsid protein of the encephalitic VEEV and EEEV has been found to form a complex that inhibits host gene transcription by blocking the trafficking of cellular proteins through the nuclear membrane (Garmashova, Atasheva et al 2007, Atasheva, Fish et al 2010. SFV and SINV have been found to inhibit host transcription via nsp2, which translocates to the nucleus and acts to degrade RNA polymerase II (Akhrymuk, Kulemzin et al 2012).…”
Section: Irgs In Alphavirus Infectionmentioning
confidence: 99%